Wpływ informacji medialnej na odtwarzanie pamięci zdarzeń - Śliwerski, Andrzej (Acta Universitatis Lodziensis. Folia Psychologica, 2008)
This article focuses on the assessment of the credibility of the witnesses’ testimony. Conway model of autobiographical memory, and the theory of incorrect attribution sources indicates that our memory is based both on the original record of events and on additional information. If the new information is incorrect, the memory may become distorted. In the first part of the article are described mechanisms of autobiographical memory, which can lead to distortions of the original memory trace. The second part are devoted to empirical verification of the hypothesis that the media information distorts the eyewitness memory of an event.